The nuclear action of crime in the criminal integral organic code (Docentes 2.0 Journal, 2020)
The investigation established the consequences of the meaning of nuclear action as a substantive element of a criminal nature in computer crimes, provided for in Book I of the recent partial reform of the Ecuadorian substantive criminal codification (2019). The objective agreed to make an interpretation in the classification of the infraction from the cyber field. The perspective transcends by the degree of subjectivity on the part of the legislator, by subjectively prescribing nuclear action. The research design is inserted in the qualitative paradigm, it had the characteristic of being of the feasible type, on an explanatory level and ordinarily the modeled method of constant comparison, the exegetical and that of the logical structures. Its purpose was to explain the behavior of one variable according to another. The results provided verifications such as that the Ecuadorian State, through the exercise of the criminal action must operationalize in exegetic terms, the adequacy of the conduct displayed in order to properly qualify it ab initio of the criminal process for the correct criminalization of the crime perpetrated. As a corollary, exegesis versus the genesis of the offender's behavior in line with the consciousness and will of the volitional act.
Keywords: Nuclear action; Cybercrime; telecommunications; telematics; computer security